2020
DOI: 10.1109/access.2020.3005303
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Tin Oxide Synaptic Device for Neuromorphic Engineering

Abstract: Neuromorphic computing offers parallel data processing and low energy consumption and can be useful to replace conventional von Neumann computing. Memristors are two-terminal devices with varying conductance that can be used as synaptic arrays in hardware-based neuromorphic devices. In this research, we extensively investigate the analog symmetric multi-level switching characteristics of zinc tin oxide (ZTO)-based memristor devices for neuromorphic systems. A ZTO semiconductor layer is introduced between a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…The review of Chakraborty et al was focused on low energy aspect of NVM and their application in energy efficient memory and computing devices 15 . Our research group has reported earlier various characteristics of low power RRAM devices in different RS materials 14,16,17 . Due to low power consumption, RRAM is considered as a dominating substituent of static random‐access memory 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The review of Chakraborty et al was focused on low energy aspect of NVM and their application in energy efficient memory and computing devices 15 . Our research group has reported earlier various characteristics of low power RRAM devices in different RS materials 14,16,17 . Due to low power consumption, RRAM is considered as a dominating substituent of static random‐access memory 10 .…”
Section: Introductionmentioning
confidence: 99%
“…This material has shown synaptic operations which can be applied for both computing paradigms of deep neural networks (DNNs) and spiking neural networks (SNNs). However, due to indium and gallium both being critical raw materials, the use of zinc-tin oxide (ZTO) has started to be considered as a reliable substitute [15][16][17][18]. There are few reports on ZTO memristive devices with synaptic capabilities [19,20], and even fewer using exclusively ZTO as their switching medium [21,22], with all sharing a common bottom electrode configuration.…”
Section: Introductionmentioning
confidence: 99%
“…However, this implies the application of the voltage to the Schottky contact. In order to use a more universal terminology, the above-mentioned switching mode is referred to as "forward set", since the set operation happens in the diode's forward directions [17].…”
Section: Introductionmentioning
confidence: 99%
“…However, power consumption per chip getting higher, joule heating becoming more serious with chip complexity, and system speed bottleneck due to serial data processing have much room to resolve [2]- [5]. In order to overcome these limits and increase the parallel computing capability more importantly valued in the massive data processing, new computing architecture has been sought and neuromorphic system is on the leading edge in recent days [6]- [9]. The neuromorphic system realizes various neural networks defined by mathematical and software approaches through hardware.…”
Section: Introductionmentioning
confidence: 99%